Public Perception and Satisfaction with Health Insurance through Sehat Insaaf Card in Punjab: Health Insurance through Sehat Insaaf Card - Shahbaz , Ferheen; Bilal Afzal, Muhammad; Huda Abbasi, Hassan; Sajjad Asghar, Raja; Muhammad, Bakht; Ashfaq, Asia; Ali Chaudhary, Nauman; Naveed Tahir, Muhammad; Saleem, Javeria; Haider, Naveed (Pakistan Journal of Health Sciences, 2023)
Sehat Sahulat program, universal health coverage for the population of Pakistan, had been implemented since 2015 and the accessibility and universality of all the services got implemented in 2020 all over Punjab. Health is the right of every person, and the Sehat Insaaf card was found to provide equal rights and benefits to all. An initiative by WHO, which provide essential health services. Objective: To find the perspective of people who availed of the Sehat Insaaf card, either for medical treatment or surgical procedure, and evaluate the level of satisfaction with the Sehat Sahulat program among the population. Methods: A Descriptive Observational Study, with a sample size of 350 calculated on the WHO calculator for survey analysis version 2.0, based on survey style questionnaire filling, to calculate the satisfaction level by Likert scale among patients and attendants, who had their treatment and surgeries in Akram Medical Complex, Lahore. The study had been conducted for 6 months, from August 2022 to February 2023. Results: Statistical tests were applied on data to evaluate the percentage and cumulative percentage of satisfaction. The overall satisfaction score was 98.765%. the cumulative percentage for satisfaction rate for surgeries was high than the medical treatments with a percentage of 89.653 for surgical procedures and 74.564% for medical check-ups. Conclusions: The Sehat Sahulat program proved a successful program facilitating in countries like Pakistan and all over Punjab, a load of patients from government tertiary care hospital had been divided, and rich and poor are equally facilitated.